2003
DOI: 10.1128/jcm.41.9.4304-4311.2003
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Detection by Real-Time PCR ofAspergillus fumigatusin Bronchoalveolar Lavage Fluids and Tissue Biopsy Specimens from Patients with Invasive Aspergillosis

Abstract: A real-time PCR method was developed and used to detect Aspergillus fumigatus mitochondrial DNA (mtDNA) in bronchoalveolar lavage (BAL) fluids and tissue biopsy specimens. The analytical sensitivity of the assay was one A. fumigatus conidium per reaction, and the assay was linear at least over 4 orders of magnitude above the detection limit. BAL fluids from 66 immunocompromised patients at risk of invasive pulmonary aspergillosis (IPA) and 33 immunocompetent controls and tissue biopsy specimens from 10 immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 35 publications
0
38
1
4
Order By: Relevance
“…A total of 19 studies published between 1993 and 2011 were included (6, 7, 15, 19-22, 24, 27-33, 38, 40, 42). All studies reported on the diagnostic accuracy of PCR in BAL fluid, and 10 studies also reported on GM in BAL fluid (15,19,24,27,28,30,31,32,33,40).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 studies published between 1993 and 2011 were included (6, 7, 15, 19-22, 24, 27-33, 38, 40, 42). All studies reported on the diagnostic accuracy of PCR in BAL fluid, and 10 studies also reported on GM in BAL fluid (15,19,24,27,28,30,31,32,33,40).…”
Section: Resultsmentioning
confidence: 99%
“…Although PCR on BAL fluid demonstrated poor specificity and standardisation, with 23% false-positive results [125,126], other studies demonstrated a higher sensitivity and specificity, up to 100 and 100%, respectively [127][128][129][130][131][132][133]. Furthermore, PCR may be too sensitive, so that the difference between colonisation and infection can often be difficult to establish [134].…”
Section: Fibreoptic Bronchoscopymentioning
confidence: 99%
“…We used our realtime PCR system (GeniQ-Asper) (17) because it is most widely used in Japan. Several authors, including Loeffler et al and Costa et al, also published excellent real-time PCR detection systems for Aspergillus DNA (9,21,26,28), and their systems might produce superior results in the diagnosis of IA, which should be addressed in future studies.…”
Section: Vol 42 2004mentioning
confidence: 99%
“…A specialized laboratory as well as an expensive assay system and reagents are also required. These problems should be addressed before PCR is widely accepted as a standard screening test for IA, although it still seems to have value in making a diagnosis when a variety of clinical samples are used (20,26,28,31).…”
Section: Vol 42 2004mentioning
confidence: 99%